Phytochemical analysis and synergistic memory enhancing effect of Bacopa monnieri with Piper nigrum - Sourabh Jain; Mohar Singh Prajapati; Aakanchha Jain; Kamal Shah; Nagendra Singh Chauhan (Journal of Future Foods, 2025)
ABSTRACT: Herbal therapy is a type of alternative or complementary medicine that uses natural ingredients to alleviate health issues including mental illness. Alzheimer's disease (AD) is a progressive neurodegenerative condition marked by a slow loss of memory coupled with shrinkage of brain tissue, localized loss of neurons, primarily in the hippocampus and basal forebrain, and decreased levels of the central cholinergic neurotransmitter acetylcholine. Bacopa monnieri is also known as brahmi which is very well known for memory enhancer and Piper nigrum is work as bioavailability enhancer which will reduce the dose frequency and increase effectiveness on other drugs. So, this study's goal was to look at the physicochemical parameters, phytochemical characteristics, and synergistic memory enhancing effect of B. monnieri with P. nigrum a natural bioenhancer on mice with scopolamine-induced learning and memory deficits. Six group of six animal were treated respectively, once daily with ethanolic extract of B. monnieri (EEBM) (200 mg/kg), ethanolic extract of P. nigrum (EEPN) 200 mg/kg, Combination of EEBM (100 mg/kg) with EEPN (100 mg/kg), donepezil 1 mg/kg via oral dosing and were given intraperitoneal (ip) injection of scopolamine 1 mg/kg daily to induce cognitive deficits. The tests for locomotor activity, stair climbing, and pole climbing were utilised to evaluate the learning and memory components. Additionally examined were dopamine, serotonin (5-HT) and other physiological elements. The results showed combination of Brahmi and black pepper shows pole climbing, actophotometer activity, staircase activity that showed better therapeutic advantages for improving mice's antiamnesic activity as compared to single extract of Brahmi. In response, the treated groups with combined extract emitted noticeably more dopamine and serotonin. When compared to illness control, the extract's ability to improve memory was highly significant (P< 0.001). These findings indicate that the combination of Brahmi and black pepper improved memory and hence could serve as a viable therapeutic target for the treatment of neurodegenerative illnesses.